Pengaruh Pengetahuan Kewirausahaan, Social Skill, dan Peluang Usaha terhadap Keberhasilan Usaha Angkringan - Akbarinasasi, Arindita; Panduwinata, Lifa Farida (Nomicpedia: Journal of Economics and Business Innovation, 2023)
There are many angkringan businesses in Sumberannyar Village, Paiton District, and Probolinggo Regency, which were originally rice stalls or coffee shops that have become angkringan businesses. The aim of the research itself is to find out and analyze whether entrepreneurial knowledge influences business success, whether social skills influence business success, whether business opportunities influence business success, and whether entrepreneurial knowledge, social skills, and joint (simultaneous) business opportunities influence business success. The research method uses quantitative methods with instrument test analysis tools, classical assumption tests, and multiple linear regression tests. The results of the research show that there is an influence of entrepreneurial knowledge on business success; there is an influence of social skills on business success; there is an influence of business opportunities on business success; and there is an influence of entrepreneurial knowledge, social skills, and business opportunities together (simultaneously) on business success.